The role of the Internet in the evolution of fraud: a historical aspect - Apsimet, Nurdaulet; Smanova, Akmaral; Utegenova , Gulzat (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
T This article presents a thorough examination of how the Internet has altered the landscape of fraud, with particular focus on increasingly sophisticated digital schemes. It examines how the internet serves both criminals and cybersecurity efforts alike. Beginning with an exploration of fraud’s historical roots from its early manifestations in pre-digital to digital times and continuing into modernity, this article details its development alongside technological progress. Utilizing various research methodologies (historical and statistical analysis), such as tracking its progression across time as well as any countermeasures implemented during that period. Significant findings of this research highlight the rise of internet-enabled fraud forms such as phishing, identity theft and cyber extortion; emphasizing their global and anonymous nature. Furthermore, research indicates the need for multidisciplinary approaches that combine technological, legislative and educational strategies in combatting internet fraud. This highlights machine learning technologies like artificial intelligence in detecting fraud along with greater public awareness campaigns to build cyber literacy literacy levels among society at large.